Effect of Baduanjin exercise combined with Jue-tone music therapy on anxiety and depression in patients with psoriasis vulgaris (健身气功八段锦联合角调式音乐对寻常型银屑病患者焦虑抑郁症状的干预效果) - HU Wei (胡薇); GONG Yonghong (龚永红) (中西医结合护理)
Objective To investigate the effect of Baduanjin exercise combined with Jue-tone Music therapy on anxiety and depression in patients with psoriasis vulgaris. Methods Totally 88 patients with psoriasis vulgaris who discharged from the hospital were randomly divided into three groups: control group (n=29), intervention group A (n=29) and intervention group B(n=30). The control group received routine follow-up after discharged from hospital, the intervention group A received Baduanjin exercise, and the intervention group B received Baduanjin exercise combined with Jue-tone music therapy. The Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS)were used to assess the anxiety and depression status of patients. Results At one month after discharge form hospital, scores of SAS and SDS in intervention group A and intervention group B were lower than those in the control group, respectively(P＜0. 05), and scores of SAS and SDS in intervention group B were lower than those intervention group A(P＜0. 05). Conclusion Baduanjin exercise combined with Jue-tone music therapy during follow-up is effective to relieve the anxiety and depression of patients with psoriasis. (目的 分析健身气功八段锦联合角调式音乐对寻常型银屑病患者焦虑抑郁症状的干预效果。方法 选取医院收治的寻常型银屑病出院患者88例为研究对象, 采用随机数字表法分为对照组(n=29)、干预1组(n=29)和干预2组(n=30), 对照组采用常规出院随访, 干预1组仅练习健身气功八段锦, 干预2组练习健身气功八段锦联合聆听角调式音乐。采用焦虑自评量表(SAS)和抑郁自评量表(SDS)评估患者焦虑抑郁程度。结果 出院后1个月时, 干预1组和干预2组SAS、SDS评分均低于对照组(P＜0. 05), 且干预2组SAS、SDS评分低于干预1组(P＜0. 05)。结论 在寻常型银屑病患者出院后采用中医特色护理手段, 可帮助患者调节不良情绪, 改善患者焦虑抑郁症状。)